Criminal Protection Orders for Women Victims of Domestic Violence: Explicating Predictors of Level of Restrictions Among Orders Issued. Issue 1 (January 2021) - Sullivan, Tami P.; Weiss, Nicole H.; Price, Carolina; Pugh, Nicole E.
Criminal protection orders (POs), with varying degrees of restrictions, are issued by the criminal justice system to enhance the safety of victims of domestic violence (DV). Limited research exists to elucidate factors associated with their issuance. Therefore, the purpose of this study was to investigate how demographic, relationship, parenting, and court-process-related factors are related to the level of restriction the PO places on the offender. Two-hundred ninety-eight women who were victims in a criminal DV case ( M age 36.4, 50.0% African American) participated in a structured interview approximately 12 to 15 months following the offenders' arraignment. Results revealed that psychological DV severity and fear of the offender in the 30 days prior to arraignment significantly predicted PO level of restriction issued. In addition, level of restriction requested by the victim significantly predicted level of restriction issued by the judge (though closer examination of the data revealed that many orders were issued at a different level of restriction than the victim requested). Other demographic, relationship, parenting, and court-process-related factors did not predict PO level of restriction issued. Findings are discussed with respect to practice and policy in the criminal justice system.